(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: Meningitis is an inflammatory condition involving the meninges of the brain and spinal cord. Acute meningitis is global burden of disease, has a high casefatality rate and survivors can have severe lifelong disability. It can have infectious causes, such as bacteria, mycobacteria, viruses, fungi, or parasites, or be associated with autoimmunity, cancer, or reactions to medication. Risk factors that predispose individuals to meningitis and epidemics include malnutrition, household overcrowding, HIV infection, absence of immunisation, indoor air pollution, and sickle cell disease. Bacterial meningitis can rapidly become fatal and lead to severe disability in those who survive. Purpose of this study was clinical study of acute meningitis in adults. Materials and methods: This cross sectional observational study was conducted in Department of medicine, Rangpur Medical College Hospital, among the 100 patients who presented with sign symptoms of meningitis. Detailed history, clinical examination and thorough investigations were done and the findings were recorded on a proforma. Data was processed and analysed with the help of computer program SPSS and Microsoft excel. Results: The mostly affected groups were 16-20 and 31-40 years. Mean age was 33.04 (±18.08 SD) years. There was an overall male preponderance with a male to female ratio 2.12:1. Fever headache, and vomiting was most common symptoms. Altered consciousness was present in 80% of cases, focal neurological deficit and rash were present in 10% cases. CSF findings are the hallmark of diagnosing various types of meningitis. Colour of CSF, glucose and protein concentration of CSF found in this study correlates with maximum authority. On evaluation of aetiology, 66% cases were due to bacteria and 24% and 10% cases were tuberculous and viral aetiology respectively. Outcome of pyogenic meningitis was good and mortality was 6%. Inspite of treatment 8 out of 24 (33%) tuberculous meningitis patient’s were died. One case of bacterial and one case of viral meningitis were missed during follow up. Conclusion: Meningitis is foremost causes of morbidity and mortality. It is recommended that provision of proper health care support, rapid detection and other investigation facilities reduce the disability. Chatt Maa Shi Hosp Med Coll J; Vol.21 (1); January 2022; Page 36-40